Integrated remote sensing and GIS approach using Fuzzy-AHP to delineate and identify groundwater potential zones in semi-arid Shanxi Province, China. (December 2020) - Shao, Zhenfeng; Huq, Md. Enamul; Cai, Bowen; Altan, Orhan; Li, Yan
Abstract: In Shanxi Province, China, groundwater is a major problem and exploration of groundwater potential zones (GWPZs) is a great necessity. This paper contributed to integrate RS-GIS to delineate GWPZ and applied Fuzzy-AHP method in a single platform. The main objective includes delineation GWPZs with RS and geo-environmental factors using Fuzzy-AHP method. Fuzzy-AHP method was employed to calculate weight of factors. RS-GIS was used to create maps and discover groundwater availability. GWPZs were classified in five separate classes. Results indicated that 13.26%, 27.02%, 26.35%, 23.64%, and 9.71% area classified as very good, good, moderate, poor, and very poor GWPZs. The validated analytical results revealed 82.5%, 12.3%, 3.5%, and 1.7% existing water wells exhibited in very good, good, moderate, and poor/very poor GWPZs. This indicates Fuzzy-AHP model generated findings were in very good agreement with ground-truth data. This RS-GIS based Fuzzy-AHP method is proficient and efficient in identification and delineation of GWPZs. Graphical abstract: Image 1 Highlights: Groundwater potential zones (GWPZs) in semi-arid area delineated with RS-GIS. Seven geo-environmental factors are used for GWPZ. RS-GIS for GWPZ and Fuzzy-AHP model are used in a single platform. Fuzzy-AHP method was employed to calculate the weight of the factors. GWPZs are classified as very good, good, moderate, poor, and very poor GWPZ.